Penguatan Kompetensi Pedagogik Guru Melalui Pelatihan Penilaian Daring Hasil Belajar Siswa - Putranto, Sumbaji; Shavira, Lintang Ega (Jurnal Pengabdian Masyarakat - PIMAS, 2024)
Improving teacher competence is something crucial to develop the quality of education. This community service is carried out as an effort to increase the pedagogic capacity of teachers, especially in carrying out online learning assessments. This training was conducted at Cahaya Bangsa Utama Middle School through a Zoom meeting which was attended by 22 participants. The training method used is active and participatory learning which includes lecture activities and practice/training where trainees can play an active role in asking each other questions, discussing, and practicing directly on the material provided. The material provided during the training includes 1) the concept of online learning assessments, 2) the principles of online learning assessments, 3) Techniques for assessing knowledge, attitudes, and skills, and 4) Application for online learning assessments. Implementation of the training can be interpreted as a success, indicated by a positive response from the training participants and an increase in participants' understanding regarding the online learning assessments.